Plastics Flammability Handbook : principles, regulations, testing and approval - Troitzsch, Jürgen, author 321082; Antonatus, Edith, author 651469; ScienceDirect (Online service) 7722 (Munich : Hanser, 2021)
Plastics flammability is a highly important consideration in many industries, including building and construction, mass transportation, electrical and electronic equipment, wire and cable, as well as upholstered furniture and textiles. This comprehensive handbook has been, since its first edition in 1983, unrivalled as the definitive source of information on the reaction of plastics to fire, as well as on the relevant regulations and testing methods. This fourth edition is comprehensively updated throughout, with inclusion of new national and international standards, new technologies and testing procedures, and novel retardants and formulations, reflecting the current state of the art. The book is edited by the internationally renowned consultant Jürgen Troitzsch and by Edith Antonatus, who have assembled leading experts to cover their specialty areas with authority within their respective chapters.